Development of an industrialised building system for facilitating 3D modular design process in Malaysia - Mamdooh, Maziyar (2012)
Industrialised Building System (IBS) is an exclusive construction method that deals with prefabricated building component (known is Malaysia as IBS Components) following by on-site installation. The method is become effective while it is harmonising and managing IBS component in a modular and repetitive manner called Modular Design Process (MOP). The method is supported insistently and requested firmly by Malaysian government from all local stakeholders. However, the IBS Survey 2005 revealed that Malaysian architects still are not willing to incorporate IBSIMDP in their common practices. The critical reason behind this hesitation is addressed: 1) because of lack of awareness from local IBS components & their qualifications; and 2) significant consistency in integration of the new design technologies such as Building Information Modelling (BIM) with the traditional approach of IBSIMDP. The analysis of literature review showed that the BIM and other similar sub-systems require 3D digital information library of building components, which is lacking in the conventional design process of MDP. Consequently, this research posited that the availability of IBS component information in 3D digital library format would encourage architects to use MDP. The literature review was conducted critical analysis to investigate the integration of MDP and BIM by reviewing the state-of-the-art projects as the Product Information Aggregators (PIAs) do. So, the research proposed to develop the IBS Interface System with exclusive functionality in aggregating and distributing IBS digital component information through a classified naming system in order to assist architects for facilitating MDP in BIM. However, three system requirements should have to be cleared before the system development process. Therefore, the research chose three sequential methods: 1) Identifying System Requirements; 2) Developing IBS Design System; and 3) Evaluating the System using Charrette Test Method (CTM). Firstly, the research found the system requirements through two qualitative interviews, which were conducted among 10 local professional architects in IBS and 50 highly experienced 3D modellers working in multinational architectural firms. The interviews resulted in three system requirements: I) Seventeen Exclusive Functionalities, 2) Ranking the IBS Component Information and 3) a Classified Component Naming (CCN) for 3D modelling practice includes an application gadget for automating the generation of CCN Codes. Secondly, the research utilised Agile System Development Method for applying system requirements into developing the IBS Interface System. The development of IBS Interface System explained how to develop: 1) A Prototype of IBS Digital Component Information Warehouse; and 2) A Framework of 3D Modular Design Process. Thirdly, the study evaluated the effectives of the new system in comparison to the conventional one by performing CTM. Three groups of architects participated to prove the positive effectiveness of the IBS interface System. Consequently, the results of each individual group were presented for verification and validation of the IBS Interface System by practicing its prototype in the proposed 3D Modular Design Framework. Eventually, the research claims on four contribution areas of knowledge: 1) converting architects' demands into tool functionalities; 2) prioritising the IBS Component Information based on architects' perspective; 3) generating the CCN for enumeration and retention ono Prefabricated Building Components; and 4) developing a new design framework for 3D MOP. Results of this study are expected to intensify the use of IBS components among the local architects in line with the national agenda of Malaysian construction industry.